Prophylactic and therapeutic vaccination with carrier‐bound Bet v 1 peptides lacking allergen‐specific T cell epitopes reduces Bet v 1‐specific T cell responses via blocking antibodies in a murine model for birch pollen allergy. Issue 2 (22nd January 2014) - Linhart, B.; Narayanan, M.; Focke‐Tejkl, M.; Wrba, F.; Vrtala, S.; Valenta, R.
Summary Background Vaccines consisting of allergen‐derived peptides lacking IgE reactivity and allergen‐specific T cell epitopes bound to allergen‐unrelated carrier molecules have been suggested as candidates for allergen‐specific immunotherapy. Objective To study whether prophylactic and therapeutic vaccination with carrier‐bound peptides from the major birch pollen allergen Bet v 1 lacking allergen‐specific T cell epitopes has influence on Bet v 1‐specific T cell responses. Methods Three Bet v 1‐derived peptides, devoid of Bet v 1‐specific T cell epitopes, were coupled to KLH and adsorbed to aluminium hydroxide to obtain a Bet v 1‐specific allergy vaccine. Groups of BALB/c mice were immunized with the peptide vaccine before or after sensitization to Bet v 1. Bet v 1‐ and peptide‐specific antibody responses were analysed by ELISA. T cell and cytokine responses to Bet v 1, KLH, and the peptides were studied in proliferation assays. The effects of peptide‐specific and allergen‐specific antibodies on T cell responses and allergic lung inflammation were studied using specific antibodies. Results Prophylactic and therapeutic vaccination with carrier‐bound Bet v 1 peptides induced a Bet v 1‐specific IgG antibody response without priming/boosting of Bet v 1‐specific T cells. Prophylactic and therapeutic vaccination of mice with the peptide vaccine induced Bet v 1‐specific antibodies which suppressed Bet v 1‐specific T cell responses and allergic lung inflammation. Conclusion and Clinical Relevance Vaccination with carrier‐bound allergen‐derived peptides lacking allergen‐specific T cell epitopes induces allergen‐specific IgG antibodies which suppress allergen‐specific T cell responses and allergic lung inflammation.